DAMPAK PENGGUNAAN INSEKTISIDA DALAM BUDIDAYA TANAMAN PADI SAWAH TERHADAP KESEHATAN PETANI: Dampak pestisida terhadap kesehatan petani - Bimasri, John; Brando, Marlon; Wartono (Universitas Muhammadiyah Bengkulu, 2024)
Pesticides are one of the main agricultural tools that if used unwisely will cause environmental pollution and health problems. The study was conducted to analyze the impact of insecticide use on rice cultivation on farmers health problems. The study was conducted in Tugumulyo District, Musi Rawas Regency, South Sumatra Province, located in Srikaton Village, Trikoyo Village, and Tegalrejo. From January to April 2024, using the Survey Method. Respondents were determined using the Simple Random Sampling method as much as 5% of the population of each research location. The data collected were in the form of types and active ingredients of insecticides, types of pests, farmer perceptions, and types of diseases suffered by farmers. The data obtained were analyzed using statistical analysis and then explained descriptively. The results showed that 47.1% of farmers used Winder 25 WP insecticide with the active ingredient Imidacloprid. There were 5 types of pests that attacked, namely brown planthoppers, bondol birds, rats, bedbugs, and stink bugs. As many as 88.7% of the community were exposed to insecticides and 52% suffered from health problems. The high environmental and health impacts that occur because the level of understanding of the impacts of insecticide use is still very low, and public knowledge of the technical use of safe insecticides is still very low, which is 16.1%. In addition, the high level of public trust in the efficacy of insecticides in killing pests also greatly influences. The conclusion of the study is the low understanding of farmers about the dangers of insecticide exposure. The environmental impacts caused are in the form of air pollution, and health problems suffered by farmers are nausea, headaches, skin, eye and nose irritation.